Divergent TCR-Initiated Calcium Signals Govern Recruitment vs. Activation of Human Alloreactive Effector Memory T cells by Endothelial Cells - Manes, Thomas D. (J Immunol, 2018)
Early human allograft rejection can be initiated when circulating human host vs. graft antigen-specific CD8 and CD4 effector memory T cells (T(EM)) directly recognize MHC Class I and II, respectively, expressed on the luminal surface by endothelium lining graft blood vessels. TCR engagement triggers both graft entry (TCR-driven transendothelial migration or TEM) and production of pro-inflammatory cytokines. Both TCR-driven TEM and cytokine expression are known to depend on T cell enzymes, myosin light chain kinase and calcineurin, respectively, that are activated by cytoplasmic calcium and calmodulin, but whether the sources of calcium that control these enzymes are the same or different is unknown. Using superantigen or anti-CD3 antibody presented by cultured human dermal microvascular cells to freshly isolated peripheral blood human T(EM) under conditions of flow, models of alloantigen recognition in a vascularized graft, we tested the effects of pharmacological inhibitors of TCR-activated calcium signaling pathways on TCR-driven TEM and cytokine expression. We report that extracellular calcium entry via CRAC channels is the dominant contributor to cytokine expression, but paradoxically these same inhibitors potentiate TEM. Instead, calcium entry via TRPV1, L-Type Ca(v), and pannexin-1/P2X receptors appear to control TCR-driven TEM. These data reveal new therapeutic targets for immunosuppression.